(untitled) (The Review of Diabetic Studies, 2023)
Remarkable progress has been made in islet transplantation over a span of 40 years. Once just an experimental curiosity in mice, this therapy has moved forward, and can now provide robust therapy for highly selected patients with type 1 diabetes (T1D), refractory to stabilization by other means. This progress could not have occurred without extensive dynamic international collaboration. Currently, 1,085 patients have undergone islet transplantation at 40 international sites since the Edmonton Protocol was reported in 2000 (752 allografts, 333 autografts), according to the Collaborative Islet Transplant Registry. The long-term results of islet transplantation in selected centers now match registry data of pancreas-alone transplantation, with 6 sites reporting five-year insulin independence rates ≥50%. Islet transplantation has been criticized for the use of multiple donor pancreas organs, but progress has also occurred in single-donor success, with 10 sites reporting increased single-donor engraftment. The next wave of innovative clinical trial interventions will address instant blood-mediated inflammatory reaction (IBMIR), apoptosis, and inflammation, and will translate into further marked improvements in single-donor success. Effective control of auto- and alloimmunity is the key to longterm islet function, and high-resolution cellular and antibody-based assays will add considerable precision to this process. Advances in immunosuppression, with new antibody-based targeting of costimulatory blockade and other TB cellular signaling, will have further profound impact on the safety record of immunotherapy. Clinical trials will move forward shortly to test out new human stem cell derived islets, and in parallel trials will move forward, testing pig islets for compatibility in patients. Induction of immunological tolerance to self-islet antigens and to allografts is a difficult challenge, but potentially within our grasp.